Exploring the matrix: knowledge, perceptions and prospects of artificial intelligence and machine learning in Nigerian healthcare - Adigwe, Obi Peter; Onavbavba, Godspower; Sanyaolu, Saheed Ekundayo (Frontiers in Artificial Intelligence, 2024)
Background: Artificial intelligence technology can be applied in several aspects of healthcare delivery and its integration into the Nigerian healthcare value chain is expected to bring about new opportunities. This study aimed at assessingto assess the knowledge and perception of healthcare professionals in Nigeria on the application of artificial intelligence and machine learning in the health sector.A cross sectionalcross-sectional study was undertaken amongst healthcare professionals in Nigeria with the use of a questionnaire. Data were collected across the six geopolitical zones in the Country using a stratified multistage sampling method. Descriptive and inferential statistical analyses were undertaken for the data obtainedusing Statistical Package for Social Sciences (SPSS) software version 25.Results: Female participants (55.7%) were slightly higher in proportion than compared to the male respondentss (44.3%). Pharmacists accounted for 27.7% of the participants, and this was closely followed by medical doctors (24.5%) and nurses (19.3%). Majority The majority of the respondents (57.2%) reported good knowledge regarding artificial intelligence and machine learning, about a third of the participants (32.2%) were of average knowledge, and 10.6% of the sample had poor knowledge. More than half of the respondents (57.8%) disagreed with the notion that the adoption of artificial intelligence in the Nigerian healthcare sector can result in job losses. Two-thirds of the participants (66.7%) were of the view that the integration of artificial intelligence in healthcare will augment human intelligence. Three-quarters (77%) of the respondents agreed that the use of machine learning in Nigerian healthcare can facilitate efficient service delivery.This study provides novel insights regarding healthcare professionals' knowledge and perception on the application of artificial intelligence and machine learning in the healthcare sector. The emergent findings from this study can guide government and policymakers in decision-making with respect to the deployment of artificial intelligence and machine learning for healthcare delivery.